RADON TEST MEASUREMENT WITH CE-DOPED YTTRIUM ALUMINUM OXIDE PEROVSKITE SCINTILLATOR - Plastino W.; de Notaristefani F.; De Felice P. (My University, 2002)
Scintillation properties of a Ce-doped yttrium aluminium oxide perovskite monocrystal optically coupled to a Hamamatsu H5784 photomultiplier are analyzed with a standard bialkali photocathode for radon and radon daughters gamma-ray spectrometry. Tests in water up to 100°C and in acidic solutions of HCl (37%), H2SO4 (48%) and HNO3 (65%) were performed to simulate environments of geophysical interest, such as geothermal and volcanic areas. Comparative measurements with standard radon sources provided by the National Institute for Metrology of Ionizing Radiations (ENEA) confirm the non-hygroscopic properties of the scintillator and small dependence of the light yield on temperature and HNO3.The Ce-doped yttrium aluminum oxide perovskite monocrystal shows high response stability for radon gamma-ray spectrometry in environments with large temperature gradients and high acid concentrations.
Keywords: Radon; radon daughters; gamma-ray spectrometry; geophysics